Development of pragmatic skills as an integral aspect in training young specialists. ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Nowadays pragmatic competence is so important. Lack of pragmatic competence may result to problem in communication such as miscommunication and misunderstanding. The utterances in miscommunication or misunderstanding may be considered rude insults. This is the main reason why students need to learn and to have the pragmatic competence to support their communication abilities. In order to teach that pragmatic competence to students, teacher, then, has to own this competence. He or she has to understand and aware of pragmatics knowledge and pragmatics competence.